The Correlation of News Exposure About Drugs and The Anxiety Level of Parents Toward The Intensity Communication of Parents and Children About Drugs - Reonell Rafendi, Mochamad; Herieningsih, MS, Dra. Sri Widowati (Interaksi Online, 2016)
Drug abuse in Indonesia has increased from year to year. Not a few reports in the mass media that provide information about drugs. The majority of drug users from among teens. This condition leads to anxiety of parents in their teens in the midst of many drug cases that happened and can happen to anyone. Anxiety can encourage parents to share information to their children about the dangers and effects of drugs. The study aims to determine the correlation of news exposure about drugs and the anxiety level of parents toward the intensity communication of parents and children about drugs. The theory used in this study is the Dependency Theory About Effects of Mass Communication and Protection Motivation Theory. Sampling technique were used is Non-Probability Sampling that is Quota sampling. Respondents in this study is parents who have teenagers aged 15-22 years old in the city of Semarang and affected by news exposure about drugs during the last two months. Analysis Kendall correlation test is used to test the hypothesis. The results of this study indicate that there is no correlation between news exposure about drugs toward the intensity communication of parents and children about drugs, where the significance value as big as 0.288. Furthermore, there is a correlation between the anxiety level of parents toward the intensity communication of parents and children about drugs, where the significance value as big as 0.016 and a correlation coefficient as big as 0.311. Then, this study provides advice to parents to be more mature in dealing with the diversity of information in the mass media, so that they get the proper information and can provide new knowledge for them.